2016
DOI: 10.1007/s10461-016-1313-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV and STI Testing and Related Factors Among Men Who Have Sex with Men in Estonia

Abstract: HIV and sexually transmitted infections (STI) testing rates among men who have sex with men (MSM) in Estonia are low. We collected data from 265 MSM in a national, online survey. Lifetime HIV testing was related to risky sexual behaviors and contacts with health care services, while lifetime STI testing was related only to contacts with health care services. In addition, some personal values were significant predictors of testing. For example, high achievement (personal success through demonstrating competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Many of these behaviors, including unprotected anal intercourse, are common in MSM ( Baggaley et al, 2010 ). Several studies have found that various preventive behaviors like screening for HIV and other sexually transmitted infections (STI), protecting sexual relations (e.g., condoms), and the use of PrEP ( Ballester-Arnal et al, 2015 ; Gu et al, 2011 ; Lakhe et al, 2019 ; McDaid et al, 2021 ; Phillips et al, 2019 ; Rüütel et al, 2016 ) are associated with many different factors. The latter include socioeconomic status (SES), which can be assessed from education level, perceived financial situation, and profession, demographic characteristics (e.g., gender, age, and place of birth or residence), social support, and health literacy (HL).…”
mentioning
confidence: 99%
“…Many of these behaviors, including unprotected anal intercourse, are common in MSM ( Baggaley et al, 2010 ). Several studies have found that various preventive behaviors like screening for HIV and other sexually transmitted infections (STI), protecting sexual relations (e.g., condoms), and the use of PrEP ( Ballester-Arnal et al, 2015 ; Gu et al, 2011 ; Lakhe et al, 2019 ; McDaid et al, 2021 ; Phillips et al, 2019 ; Rüütel et al, 2016 ) are associated with many different factors. The latter include socioeconomic status (SES), which can be assessed from education level, perceived financial situation, and profession, demographic characteristics (e.g., gender, age, and place of birth or residence), social support, and health literacy (HL).…”
mentioning
confidence: 99%